The effects of competition on medical service provision - Jeannette Brosig-Koch; Burkhard Hehenkamp; Johanna Kokot (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We explore how competition between physicians affects medical service provision. Previous research has shown that, in the absence of competition, physicians deviate from patient-optimal treatment under payment systems like capitation and fee-for-service. While competition might potentially eliminate or reduce these distortions, physicians usually interact with each other repeatedly over time. This leaves scope for collusive behavior. Moreover, only a fraction of patients switches providers at all. Both patterns might prevent competition to work in the desired direction. To analyze the behavioral effects of competition, we develop a theoretical benchmark which is then tested in a controlled laboratory experiment. Experimental conditions vary regarding physician payment (fee-for-service vs. capitation) and the severity of patients' illness (low vs. high). In our setting, two physicians repeatedly treat patients from a homogeneous patient population. While half of the patients always attend the physician providing the highest patient benefit, the other ones always visit the same physician. Treatment decisions made in the experiment affect real patients' health. Our results reveal that, in line with the theoretical prediction, introducing competition can reduce overprovision and underprovision, respectively. The observed effects depend on patient characteristics, though. Compared to related experimental research on price competition, collusive behavior is less frequently observed in our setting of medical service provision.
Keywords: I10; C91; C72; 330